Upaya Meningkatkan Prestasi Belajar Fiqih Melalui Materi Zakat dengan Model Pembelajaran Experience Skill Siswa Kelas IX-2 MTs Negeri Samarinda Tahun Pelajaran 2022/2023 - Asnan, Asnan (PT Literasi Nusantara Publisher, 2023)
The main factor that causes students to have difficulty learning fiqh is a lack of motivation, both internal and external motivation. This can be seen from the learning process that pays attention to teachers who provide zakat material. This study aims to find out the efforts to increase learning achievement in fiqh with zakat material for class IX-2 MTs Negeri Samarinda through the application of the Experience Skill Learning Model. The results showed that the cognitive ability of class IX-2 students at MTs Negeri Samarinda was very good, as evidenced by the responses of students who showed an exemplary attitude while participating in teaching and learning activities in the field of Fiqh. In the first cycle, some students seemed active in learning activities. Then, after the implementation of the Experience Learning learning model, students are seen to be more active and responsive to zakat material. The application of the Experience Learning model at the beginning of the meeting was ineffective because students had never participated in learning activities with that model. Then the learning model is applied through group discussion activities, direct practice and reflecting on actions in each cycle. The application of this model goes well along with the ongoing learning and teaching activities involving student participation as Student Oriented. The achievement of the cognitive ability of class IX-2 MTs Negeri Samarinda experienced a significant increase after learning the field of Fiqh using the Experience Learning model.